The applications of animal models in phage therapy: An update. Issue 1 (31st December 2023) - Mehmood Khan, Fazal; Manohar, Prasanth; Singh Gondil, Vijay; Mehra, Nancy; Kayode Oyejobi, Greater; Odiwuor, Nelson; Ahmad, Tauseef; Huang, Guangtao
ABSTRACT: The rapid increase in antibiotic resistance presents a dire situation necessitating the need for alternative therapeutic agents. Among the current alternative therapies, phage therapy (PT) is promising. This review extensively summarizes preclinical PT approaches in various in-vivo models. PT has been evaluated in several recent clinical trials. However, there are still several unanswered concerns due to a lack of appropriate regulation and pharmacokinetic data regarding the application of phages in human therapeutic procedures. In this review, we also presented the current state of PT and considered how animal models can be used to adapt these therapies for humans. The development of realistic solutions to circumvent these constraints is critical for advancing this technology.